2021
DOI: 10.14283/jpad.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Distractions during Unsupervised Remote Digital Cognitive Assessment

Abstract: The current demand for cognitive assessment cannot be met with traditional in-person methods, warranting the need for remote unsupervised options. However, lack of visibility into testing conditions and effort levels limit the utility of existing remote options. This retrospective study analyzed the frequency of and factors associated with environmental distractions during a brief digital assessment taken at home by 1,442 adults aged 23-84. Automated scoring algorithms flagged low data capture. Frequency of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…We have previously observed lower performance on other self‐administered cognitive measures at home versus in clinic 30 . Madero et al 31 . similarly reported the presence of distraction in a minority of remote cognitive assessment sessions (7%), which had a negative impact on performance.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We have previously observed lower performance on other self‐administered cognitive measures at home versus in clinic 30 . Madero et al 31 . similarly reported the presence of distraction in a minority of remote cognitive assessment sessions (7%), which had a negative impact on performance.…”
Section: Discussionmentioning
confidence: 71%
“…We have previously observed lower performance on other self-administered cognitive measures at home versus in clinic. 30 Madero et al 31 similarly reported the presence of distraction in a minority of remote cognitive assessment sessions (7%), which had a negative impact on performance. Future work will examine whether participant self-report of interference can help reduce variability introduced by testing in an unsupervised environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial launch of the first online experiments, multiple studies have suggested that computerised online assessment can provide results that are reliable and comparable to laboratory assessment across different cognitive domains (such as working memory, executive functioning, episodic memory, verbal fluency, attention, vigilance, or complex psycholinguistic abilities), and even for full-scale neuropsychological test batteries such as the Cambridge Neuropsychological Test Automated Battery or the Cognitive Function Test (Backx et al, 2020;Feenstra et al, 2017;Kim et al, 2019;Luna et al, 2020;Trustram Eve & de Jager, 2014). However, certain studies have also highlighted that performance significantly varies between the two settings, that participants are more distracted during self-assessment, and that currently most online batteries lack normative data (Al Baghal, 2019;Gates & Kochan, 2015;Madero et al, 2021). This underlines the need for more research on the utility, comparability, and reliability of online assessments.…”
mentioning
confidence: 99%
“…If cognitive screening / risk for cognitive decline is the goal, worse performance in remote settings may help identify risk in a way not captured by controlled clinical settings, adding an element of ecological validity in terms of ability to adapt to a new task without assistance. Future work will examine whether and to what degree these factors may influence test performance, as increased distractions in the home environment can negatively impact performance 58 . Finally, while use of a strictly biomarker-defined ground truth is a novel aspect of this study, in vivo PET biomarkers also have some limitations such as high but imperfect reliability (manifested by "noise" in the trajectories of imaging results over time in some individuals), and the fact that PET measures of amyloid and tau pathology have a sensitivity floor and medically significant pathology can exist that lies beneath this detection threshold 59 .…”
Section: Discussionmentioning
confidence: 99%